The use of biotelemetry to explore disease progression markers in amyotrophic lateral sclerosis - Kelly, M; Lavrov, A; Garcia-Gancedo, L; Parr, J; Hart, R; Chiwera, T; Shaw, CE; Al-Chalabi, A; Marsden, R; Turner, M; Talbot, K (Taylor & Francis, 2020)
Objective: To explore novel, real-world biotelemetry disease progression markers in patients with amyotrophic lateral sclerosis (ALS) and to compare with clinical gold-standard measures.